Tracking The User’s Behaviour in E- Commerce Website - Gupta, Smriti; Kumari, Komal; A, Latha (International Journal of Computer Sciences and Engineering, 2025)
Online shopping is becoming more and more common in our daily lives. Tracking user’s interests and behaviour is essential in order to fulfil customer’s requirements. The information about user’s behaviour is stored in the web server logs. Absorbing a view of the process followed by user’s during a session can be of great interest to identify the behavioural patterns. The analysis of such information has focused on applying data mining techniques. Data mining is the process of sorting through large data sets to identify patterns and establish relationships to solve problems through data analysis. It is a process used by companies to turn raw data into useful information. By using software to look for patterns in large batches of data, businesses can learn more about their customers to develop more effective marketing strategies, increase sales and decrease costs. To address this issue, in this work we proposes a linear temporal logic model checking method for the analysis of structured e-commerce web logs.